Uma démarche participada de avaliação de Projectos Curriculares de Turma - Virgílio Rego da Silva; Vânia Betina Coutinho (Universidade do Minho, 2005)
This text presents the results of an evaluation experience of class curricular projects, developed in 32 classes by the group of teachers in each class of the Grammar School 2/3 Frei Caetano Brandão, in the school year 2003/04. Its an evaluation study based on a theoretical framework that considers the school and the project problematics, the pedagogical view of projects and the internal evaluation process of schools. In this text, a methodological device is defined which contemplates the planning of the inquiry, the projects evaluation criteria and the analysis techniques used. The results are presented and some conclusions and suggestions/ recommendations for the future work are drawn, in relation to the curriculum construction.